2015
DOI: 10.1089/aivt.2014.0011
|View full text |Cite
|
Sign up to set email alerts
|

“Open Source”–Based Engineered Human Tissue Models: A New Gold Standard for Nonanimal Testing Through Openness, Transparency, and Collaboration, Promoted by the ALEXANDRA Association

Abstract: Today, engineered three-dimensional tissue models from human cells of the skin, cornea, mucosa, and respiratory tract are widely used in pharmaceutical, chemical, consumer, and cosmetic industries as alternatives to animal testing. The currently available scientifically valid 3D tissue-engineered models, however, are protected by patents and/or are being commercialized using proprietary tissue culture procedures owned by only a few private companies. As a consequence, their continued commercial availability mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…Their study also showed that conidia applied at low density were less prone to extend into deep layers after 4 days of infection. Using our “Open Source” RHE model recommended for nonanimal testing due to its openness, transparency and collaborative development, it appeared that several dermatophyte species and strains remained restricted to the cornified layer after 4 days of infection at densities selected for infection …”
Section: Reconstructed Human Epidermis Allows To Characterize Barriermentioning
confidence: 99%
“…Their study also showed that conidia applied at low density were less prone to extend into deep layers after 4 days of infection. Using our “Open Source” RHE model recommended for nonanimal testing due to its openness, transparency and collaborative development, it appeared that several dermatophyte species and strains remained restricted to the cornified layer after 4 days of infection at densities selected for infection …”
Section: Reconstructed Human Epidermis Allows To Characterize Barriermentioning
confidence: 99%
“…In our study, the FT 3D skin provided a reproducible in vitro test system for sensor development and characterization. Such skin equivalents represent a reliable tool in chemical and pharmacological research [ 22 , 23 ]. However, FT 3D skin does only partially resemble the complexity of native skin.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to native skin samples, tissue-engineered skin equivalents of different complexity—from simple epidermal models to multi-layered full-thickness skin tissues—can be generated [ 21 ]. These represent standardized model systems due to their capacity to resemble skin anatomy and physiology [ 22 ], and are, for instance, used in pharmacological drug development [ 23 ]. In contrast to measurements performed in vivo or ex vivo on excised skin samples, skin equivalents further allow investigating the influence of distinct skin layers on the measurement to fully understand underlying mechanisms of signal generation.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil intends to ban animal use in research in the near future and, in an attempt to reduce these trials, started with the recognition of some validated OECD alternative methods to animal use (Brasil, 2014), including two RHE models (OECD TG 431 and 439). However, the validated models are produced abroad and are inaccessible by importation in Brazil due to logistics and customs issues (De Wever et al, 2015). Thus, the development of new RHE models provides independence for small companies.…”
Section: Discussionmentioning
confidence: 99%
“…For cosmetic industries in developing countries such as Brazil, where customs problems often prevent the importation of commercial kits, an open-source protocol that can be used for toxicological assays is critical (De Wever et al, 2015). This tool can provide autonomy and enable progress in the establishment of alternative methods to animal testing.…”
Section: Introductionmentioning
confidence: 99%